Phagosyncope: an unusual presentation of airway malfunction due to acquired laryngomalacia in an elderly Indian male - Suresh, Indrajit; Challa, Suhas; Gattavadi, Sanjana Narendran (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Acquired laryngomalacia is an uncommon entity in adults. It may often be misdiagnosed, under-reported or confused with respiratory diseases such as bronchial asthma. The exact pathogenesis of acquired laryngomalacia remains poorly understood, although many at-risk groups have been identified. High pitched inspiratory stridor which worsens with physical exertion is often encountered in patients. Predominantly being a mechanical issue, wherein supraglottic structures occlude the airway, causing respiratory distress and hypoventilation, adult laryngomalacia may cause choking episodes. In the elderly, where mucosal laxity and poor neuromuscular control may be encountered, a possibility of this illness must be kept in mind in those presenting with respiratory symptoms. Supraglottoplasty remains the best mode of treatment currently and has a high success rate. The authors report a case of acquired laryngomalacia in an elderly male, who presented with an unusual cluster of complaints. He underwent detailed evaluation for confirmation of his diagnosis and underwent surgical correction, which ameliorated his condition.